SPE International Symposium on Formation Damage Control 2000
DOI: 10.2118/58772-ms
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Perforating Strategy in Well Completions to Maximize Productivity

Abstract: The Britannia field is a gas producing reservoir operated jointly by Chevron and Conoco. Prior to completion of the wells, two major concerns were raised: potential sand production (perforation stability), and the optimum underbalance (for zero perforation skin) during completion. Theoretical models were used to predict the optimum underbalance based on log derived formation properties. Using detailed log permeability data numerous simulations were carried out to choose the gun, charges, shot density and perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2000
2000
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
2
0
2
Order By: Relevance
“…Substitute the series into the equation. 6. Identify the zeroth component p 0 as the terms arising from the given conditions and from integrating the source term.…”
Section: Essential Steps In the Adomian Decomposition Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Substitute the series into the equation. 6. Identify the zeroth component p 0 as the terms arising from the given conditions and from integrating the source term.…”
Section: Essential Steps In the Adomian Decomposition Methodsmentioning
confidence: 99%
“…However, as early as in 1950, experimental studies indicated that, with proper penetration and shot density, the flow efficiency of a perforated system should be higher than that of a comparable-length openhole completion [2,3]. Unfortunately, even with proper geometry, experimental and field performance fell short of predicted results [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…現在,鋼管の穿孔には成形爆薬を用いたガンパーフォ レーターが広く用いられている (例えば, Halleck, (1997) , Kusaka et al, (1998) ,Eller et al, (2002) ,Underdown et al, (2003 and Colwell et al, (2006) ) 。しかしながら,爆 薬を用いる方法で同一面上に複数個の穿孔を行うと,対 象が小径鋼管でまた腐食が進み強度が低下している場 合,鋼管を分断する恐れがある (Allen et al, (1982) (3)…”
Section: との隙間をセメンチングするなどの目的である。unclassified
“…Los punzados desempeñan un papel fundamental en la producción de hidrocarburos, desde las pruebas de pozos para la evaluación del yacimiento hasta la completación e intervención de remediación o reacondicionamiento del pozo, constituyendo un elemento clave para el éxito de la exploración y explotación, la optimización económica en la producción del pozo de petróleo y/o gas, la productividad del pozo a largo plazo y la recuperación eficiente de los hidrocarburos. Para efectuar esta operación, el diámetro del pozo condicionará el diámetro exterior de los cañones y, de acuerdo a este, tendrán mayor o menor penetración en el revestimiento y la formación [16], [24], [30], [32], [33].…”
Section: Operación De Estimulación Hidráulica Para La Producción De H...unclassified